PENERAPAN STRATEGI PEMBELAJARAN QUICK ON THE DRAW UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA SISWA KELAS II D SDN 01 KOTA PADANG SIDIMPUAN - Torang Siregar; Almira Amir; Anita Adinda; Mariam Nasution (Jurnal Pendekar Nusantara, 2023)
This study aimed to improve a) the activities of teachers and students,b) interest in learning mathematics students, c) the results of mathematics learning students of class II D SDN 01 Kota The research method was classroom action research. This research was conducted in class II D SDN 01, Padangsidimpuan City consisting of 25 students. The results of this study were an increase in teacher activity in the first cycle obtained an average score of 22.5, increased in the second cycle with an average score of 24.5, and increased in the third cycle to 28.5. Increased activity of students in the first cycle obtained an average score of 25.5, and increased in the second cycle to an average score of 27, and then increased again in the third cycle to 31.5. In students' interest in learning mathematics in the first cycle the percentage was 77.6%, increasing in the second cycle by 86%, increasing again in the third cycle to 89.2%. The improvement of cognitive cognitive learning outcomes of students in the first cycle was average value (66.4) with classical learning completeness (44%), increased in the second cycle the average score (01.4) and classical learning completeness (64%), increased in cycle III (80.6) and classical learning completeness (88%). Then it could be concluded that the application of quick on the draw learning strategies could increase the interest and results of learning mathematics of students in class II D SDN 01 Kota Padangsidimpuan.